Prevalence of Blood-Borne Viruses in Health Care Workers of a Northern District in Pakistan: Risk Factors and Preventive Behaviors - Muhammad Zuhaib Khan; Shahab Saqib; Sayed Irtiza Hussain Shah Gardyzi; Javaria Qazi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Blood-borne viral infections like viral hepatitis are highly prevalent in Pakistan. There is also a potential threat of human immunodeficiency virus (HIV) spread in the country. Health care workers (HCWs) are a high risk population for acquiring such viral infections and potential spread to the patients. This study aimed to determine the frequency of three blood-borne viruses: HCV, HBV, and HIV in HCWs of district Malakand in northern Khyber Pakhtunkhwa (KPK) province of Pakistan. Moreover, risk factors and preventive behaviors among HCWs were investigated in detail. Materials and Methods. Prevalence was investigated using serological assays followed by real time polymerase chain reaction (RT-PCR) based characterization. A total of 626 health care workers working at 17 different health care units, belonging to 6 different job categories, were included in this study. Results. HIV was not detected in the HCWs while rate of prevalence of HCV and HBV was far less (0.8 % and 0.64 %, resp.) as compared to general population (4.7%–38%). The majority of HCWs were aware of the mode of spread of these viruses and associated risk factors. Needle stick injury was found to be the most important risk factor for possible acquisition of these infections.